2023
DOI: 10.1038/s41467-023-36364-9
|View full text |Cite
|
Sign up to set email alerts
|

Widespread contribution of transposable elements to the rewiring of mammalian 3D genomes

Abstract: Transposable elements (TEs) are major contributors of genetic material in mammalian genomes. These often include binding sites for architectural proteins, including the multifarious master protein, CTCF, which shapes the 3D genome by creating loops, domains, compartment borders, and RNA-DNA interactions. These play a role in the compact packaging of DNA and have the potential to facilitate regulatory function. In this study, we explore the widespread contribution of TEs to mammalian 3D genomes by quantifying t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 85 publications
3
18
0
Order By: Relevance
“…These findings are in line with a previous study that reported higher CTCF binding site clustering and stronger CTCF affinity at TAD boundaries shared across five murine species, compared to boundaries with lower conservation 50 . Moreover, CTCF binding sites at ultraconserved boundaries overlap with older transposable elements (namely MIRs), whereas human-specific boundaries are associated with more recent families (ERVs), reinforcing the notion that different waves of transposable elements have been shaping genome topology through insertion of CTCF binding sites at different evolutionary times 24,26,29 . Altogether, this shows that recurrent emergence and maintenance of several, possibly redundant, CTCF binding sites contribute to the higher conservation and insulation strength of ultraconserved TAD boundaries.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…These findings are in line with a previous study that reported higher CTCF binding site clustering and stronger CTCF affinity at TAD boundaries shared across five murine species, compared to boundaries with lower conservation 50 . Moreover, CTCF binding sites at ultraconserved boundaries overlap with older transposable elements (namely MIRs), whereas human-specific boundaries are associated with more recent families (ERVs), reinforcing the notion that different waves of transposable elements have been shaping genome topology through insertion of CTCF binding sites at different evolutionary times 24,26,29 . Altogether, this shows that recurrent emergence and maintenance of several, possibly redundant, CTCF binding sites contribute to the higher conservation and insulation strength of ultraconserved TAD boundaries.…”
Section: Discussionmentioning
confidence: 81%
“…Transposable elements (TEs) can introduce CTCF binding sites upon their insertion in host genomes 24 and as such, their co-option may have contributed to the evolution of TAD boundaries 25,26 . Analysis of CTCF binding sites located inside TAD boundaries in each species, showed that over half of them overlap TEs across species (ranging from 53-77%, depending on species; Extended data Fig.…”
Section: Transposable Elements Contribute To the Evolution Of Conserv...mentioning
confidence: 99%
“…Transposable elements (TEs) are ubiquitous mobile elements within eukaryotic genomes, and play major roles in both genome architecture and the generation of genetic variation (Chénais et al 2012). As a result of their insertional and recombinational activities, TEs are viewed as a major contributor to the generation of novel mutations within a genome (Choudhary et al 2023). For instance, an estimated 50–80% of all mutation events in the fruit fly, Drosophila melanogaster , are caused by TEs (Green 1988).…”
Section: Introductionmentioning
confidence: 99%
“…The genome organization subjects to different levels of regulation, such as transcription, DNA damage, DNA looping factors, epigenetic modifications, and so forth 20,55–60 . Due to the critical role of genome organization in gene transcriptional regulation, it is not surprising that viruses take advantage of the host machinery to regulate host genome organization to facilitate their survival and transmission.…”
Section: Introductionmentioning
confidence: 99%
“…[51][52][53][54] The genome organization subjects to different levels of regulation, such as transcription, DNA damage, DNA looping factors, epigenetic modifications, and so forth. 20,[55][56][57][58][59][60] Due to the critical role of genome organization in gene transcriptional regulation, it is not surprising that viruses take advantage of the host machinery to regulate host genome organization to facilitate their survival and transmission. Some viruses, like retroviruses, integrate their genome into the host cell genome to alter the genome structure and disrupt the normal function of host genes.…”
mentioning
confidence: 99%